2011
DOI: 10.1371/journal.pone.0016933
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin Gene Defects Are Independent Risk Factors for Atopic Asthma in a Polish Population: A Study in ECAP Cohort

Abstract: Background FLG null variants of which 2282del4 and R501X are the most frequent in Caucasians are established risk factors for atopic dermatitis (AD) with an effect probably mediated through impairment of epidermal barrier. Among subjects with AD FLG defects are also consistently associated with asthma and allergic rhinitis (AR) but it is less clear to what extent these associations are also present independently from skin disease. The aim of the present study was to evaluate the role of 2282del4 and R501X in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 20 publications
(33 reference statements)
5
44
2
2
Order By: Relevance
“…Although the potential role of FLG mutations as a major predisposing factor for atopic eczema has received considerable attention in recent years, to date there were only two studies investigating FLG mutations R501X, 2282del4 in Polish adults and older children. 15,16 In our results, we found a significant association between the combined genotype of all 4 FLG mutations and the susceptibility to eczema. The frequency of 2282del14 deletion showed a similar trend, although the statistical significance of this association was borderline.…”
Section: Discussionsupporting
confidence: 57%
“…Although the potential role of FLG mutations as a major predisposing factor for atopic eczema has received considerable attention in recent years, to date there were only two studies investigating FLG mutations R501X, 2282del4 in Polish adults and older children. 15,16 In our results, we found a significant association between the combined genotype of all 4 FLG mutations and the susceptibility to eczema. The frequency of 2282del14 deletion showed a similar trend, although the statistical significance of this association was borderline.…”
Section: Discussionsupporting
confidence: 57%
“…Other authors [35], refer a correlation of log10 serum IgE levels and rs7534334 in a group of asthmatic patients being the mutant genotype (TT) in patients, those with higher levels of IgE comparing with controls (TT) and comparing with wild type genotype (CC) in patients (3.49 ± 0.91 vs 2.43 ± 0.52 vs 2.92 ± 0.59) .This point to the works who showed that when skin barrier function is compromised even without skin disease there is an increased incidence of atopic disease [28].…”
Section: Discussionmentioning
confidence: 75%
“…This barrier defect could be present even in the absence of eczema [26,28,33,47], which could help us to understand the physiopathology of AD associated with LELP1 polymorphism [rs7534334] and other polymorphisms located on genes of EDC complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of FLG mutation with atopic march has been reported in cases involving pediatric asthma (Muller, et al, 2009), peanut allergy (Brown, et al, 2011), atopic asthma (Poninska, et al, 2011), allergic rhinitis (Poninska, et al, 2011) and nickel allergy (Novak, et al, 2008). In addition, epidemiological studies have identified extremely significant statistical association between FLG mutation and AD.…”
mentioning
confidence: 99%